2020
DOI: 10.1002/fsn3.1962
|View full text |Cite
|
Sign up to set email alerts
|

Feeding practice, energy, and nutrient intake adequacy among children aged 6–23 months in Southern Ethiopia: a community based cross‐sectional study

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 18 publications
(48 reference statements)
3
8
1
Order By: Relevance
“…Another study conducted in southern Ethiopia found that grains, roots and tubers are the primary staples of children aged 6–23 months ( 28 ) . Meanwhile, animal-source foods such as meat, dairy products and eggs are consumed only by a small proportion of children in the present study, which is consistent with studies conducted in other parts of Ethiopia ( 29 , 30 – 32 ) . Similarly, animal-source food consumption is lower in sub-Saharan African countries than in other parts of the world ( 22 ) .…”
Section: Discussionsupporting
confidence: 92%
“…Another study conducted in southern Ethiopia found that grains, roots and tubers are the primary staples of children aged 6–23 months ( 28 ) . Meanwhile, animal-source foods such as meat, dairy products and eggs are consumed only by a small proportion of children in the present study, which is consistent with studies conducted in other parts of Ethiopia ( 29 , 30 – 32 ) . Similarly, animal-source food consumption is lower in sub-Saharan African countries than in other parts of the world ( 22 ) .…”
Section: Discussionsupporting
confidence: 92%
“…This study revealed that 61.2% (95% CI: 58.7, 63.7) of children aged 6-23 months had poor consumption of foods rich in vitamin A in Ethiopia. This nding is in line with a study conducted in Ethiopia using EDHS 2016 (62.30%) and a study conducted in the southern part of Ethiopia (62.2%) (21). This study's ndings were greater than those of the Kenya DHS 2014 (28%) (22) and Ghana (48%) studies (23).This disparity could be due to socio-demographic and cultural variances.…”
Section: Discussionsupporting
confidence: 89%
“…The recommended energy intake from complementary foods varies according to the age of child, amount of breast milk consumed, fat content in breast milk and the frequency of feeding (Feyisa et al, 2020). For children aged 6-8, 9-11 and 12-23 months and are breastfed, it is recommended that they take 202, 307 and 548 kcal per day, respectively (Abeshu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%